2008
DOI: 10.1166/jnn.2008.370
|View full text |Cite
|
Sign up to set email alerts
|

Size and Distribution: A Comparison of XRD, SAXS and SANS Study of II–VI Semiconductor Nanocrystals

Abstract: The uniqueness of size dependent functional properties of II-VI semiconductor nanocrystals have led to the development of various techniques for determination of shape, size and distributions, although the accurate measurements of the particle sizes has always been a fundamental task in nanoscience and even become more crucial with the discovery of quantum confinement effect. A comparison of the well established techniques X-ray diffraction (XRD), small angle X-ray scattering (SAXS) and small angle neutron sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Approximating a two step model to the data results in a core radius of 2.1 nm and a total radius of 4.0 nm, which corresponds to a shell thickness of 1.9 nm, which matches well with a previous finding in literature [32]. As also reported by Keshari and Pandey [19], the core radius is again in good agreement with XRD data and the results from SAXS on the solid material, while the organic shell is now found to be considerably thicker. This is consistent with singular dissolved nanoparticles and a ligand shell with almost stretched molecules.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Approximating a two step model to the data results in a core radius of 2.1 nm and a total radius of 4.0 nm, which corresponds to a shell thickness of 1.9 nm, which matches well with a previous finding in literature [32]. As also reported by Keshari and Pandey [19], the core radius is again in good agreement with XRD data and the results from SAXS on the solid material, while the organic shell is now found to be considerably thicker. This is consistent with singular dissolved nanoparticles and a ligand shell with almost stretched molecules.…”
Section: Resultssupporting
confidence: 89%
“…In this context, small angle X-ray scattering (SAXS) is a valuable complementary method analysing a larger amount of the sample. Although data analysis and interpretation are laborious and sometimes difficult, SAXS is a well suited method for investigating the size, shape and distribution for nanoparticles in the solid state [19] but also in solution [20]. This latter point is of special interest as many applications require stable and well dissolved nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The sizes obtained from SAXS are in well agreement with those computed using the Sherrer's equation from XRD broadening. It is already reported [24] that for very small particles, the sizes obtained from XRD to SAXS are well agreed.…”
Section: Resultssupporting
confidence: 69%
“…2(a) shows the initial (raw) SAXS scattering intensity profile of prepared CdS semiconductor nanocrystals in the pepsin solution at different Rx temperatures. It clearly shows that slope of the scattering profile increases with decreasing temperature; it means that sizes get also reduced and distribution becomes narrower [24]. The details about the SAXS can be found elsewhere [25,26].…”
Section: Resultsmentioning
confidence: 90%
“…So, the intense peak at 520 nm in sample A and C corresponds to the transition from Cd ions related defect states (E -D e ) present in between the band gap. Luminescence characteristics of ZnS:Mn 2 + has been extensively studied by several groups [15,[31][32][33]. Bhargava et al [34] reported that in Mn 2 + -doped ZnS nanoparticles, very strong hybridization occurs between the sp levels of Zn and d levels of Mn 2 + ions and it results the crystal field splitting of Mn 2 + levels in between the bands of host material.…”
Section: Resultsmentioning
confidence: 99%